Analisis Kinerja Keuangan terhadap Nilai Perusahaan Sub Sektor Rokok yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2018-2022 - Titus Gustiagung Grace Widya Arta; Hwihanus Hwihanus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Evaluation of a company's financial performance is a very crucial aspect for understanding the financial condition of a business entity, as well as providing insight into the company's level of success during a certain period. This assessment also functions as an evaluation tool for management. In this research, the data used comes from the financial reports of companies operating in the cigarette subsector and listed on the Indonesia Stock Exchange during the 2018-2022 period. The data analysis method applied in this research involves financial ratio analysis, which includes liquidity ratios, solvency ratios , and profitability ratios. To analyze the data, this research uses a Partial Least Square approach, which consists of an inner model, an outer model, and a weight relationship. The research results show that the liquidity ratio has a positive but not significant influence on company value. On the other hand, profitability ratios have a positive and significant influence on company value. However, the solvency ratio shows an insignificant negative effect on company value.